Optimal timing of pharmacoinvasive strategy and its impact on clinical and economic outcomes in patients with ST-elevation myocardial infarction: a real-world perspective - Stephanus, Andrea Dias; Santos, Alice Pacheco; Rodrigues da Cunha, Ana Carolina Machado; Rocha, Ana Carolina Augusto; Meireles, Amanda de Amorim; de Oliveira, Mariana Guimarães Souza; Matsunaga, Pietra Arissa Coelho; Soares, Alexandre Anderson de Sousa Munhoz; Nogueira, Ana Claudia Cavalcante; Guimarães, Adriana de J. B. de Almeida; Alexim, Gustavo de Almeida; Campos-Staffico, Alessandra M.; et al. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundThe pharmacoinvasive (PhI) strategy is the standard-of-care for ST-elevation myocardial infarction (STEMI) patients when primary percutaneous coronary intervention (pPCI) is unfeasible. Optimal timing for post-fibrinolytic PCI (lysis-PCI) remains elusive. Therefore, this study aimed to assess the clinical and economic impacts of early vs. delayed lysis-PCI in patients with STEMI.MethodsThis retrospective cohort study included 1,043 STEMI patients classified by lysis-PCI timing. The primary outcome was in-hospital major adverse cardiovascular events (4p-MACE), with secondary outcomes such as 3p-MACE, in-hospital mortality, and costs. Multivariable logistic regression models were used to assess the association between lysis-PCI timing and outcomes. Cost analyses were conducted from the perspective of Brazilian public healthcare system, with values converted to international dollars (Int) for broader applicability.ResultsEvery 4-h delay in lysis-PCI was associated with a 44% reduction in in-hospital mortality [OR = 0.560 (95% CI: 0.381–0.775); p = 0.001] and a 13% decrease in 4p-MACE [OR = 0.877 (95% CI: 0.811–0.948); p = 0.001]. Additionally, 4-h delay in lysis-PCI was also associated with a significant reduction in in-hospital costs (Int916.20 ± 99) and disease-induced years of productivity lost (β = −41.79 ± 151 years; p = 0.001). These significant trends remained consistent even after adjusting for confounders and applying propensity score matching. Older adults (aged ≥80) experienced an increase in 3p-MACE with earlier lysis-PCI.ConclusionDelaying lysis-PCI was found to be associated with reduced in-hospital cardiovascular adverse events and lower costs, particularly among older adults. Further research should develop evidence-based lysis-PCI protocols that optimize both clinical outcomes and cost-effectiveness.